Independent Gamma Variables of McKay Distribution for Rainfall Model - Roslinazairimah, Zakaria; Nor Hafizah, Moslim (Science & Knowledge Research Society, 2015)
The application of mathematical models of rainfall is crucial in order to have a better understanding in terms of rainfall characteristics. The rainfall models has been used widely to improve water management, to construct hydrological structures and as an input in climatological studies. In this study, the gamma distribution is used to fit the marginals of monthly rainfall data. The parameters of gamma distributions, shape and scale, are estimated using the maximum likelihood estimation method. Then the sum of monthly rainfall amount is modelled using the Mckay ditribution for independent gamma variables.